Evaluación de tecnoestrés en los estudiantes de Ingeniería Industrial de la UNACH en el período 2023 – 2S. - Samaniego Vizcaíno, Adriana Alejandra (2024)
The main objective of this research study was to focus on technostress which is the intensive use of technology in the educational field has significantly transformed the dynamics of learning which leads students to adapt to this new mode of study, however, this adaptation often occurs in inadequate work spaces, Thus, we seek to evaluate the levels of technostress of the students of Industrial Engineering at UNACH in the period 2023-2S by applying a pilot test of the RED/ICT instrument to determine the reliability and reliability of the test by means of Cronbach's alpha and KMO; being feasible to apply it was surveyed to a sample of 120 students of the career, being able to identify the technostress and its dimensions: fatigue, anxiety, skepticism and inefficiency, under the criteria of high, medium and low levels. In this context, this study has a non-experimental descriptive quantitative approach. The results show that 52.5% of the students present a low level of technostress, 10% of students with a high level of technostress and 37.5% in a medium level with a tendency to increase to a high level, in addition there is a strong relationship between the variables of age and gender with respect to the dimensions of technostress; for this reason, a manual of preventive measures for the phenomenon of technostress is created, given the importance of improving aspects such as the acquisition of digital skills and the application of emotional self-regulation in students, to minimize psychosocial risks in the student community of the university career.